OPTIMALISASI SOCIAL COMMERCE SEBAGAI STRATEGI PEMASARAN BAGI UMKM DI ERA MARKETING 4.0 - Aristana, I Dewa Gede Aristana; Rahmantari, Ni Luh Laksmi; Utari, Ni Komang Mela Tri (Universitas Tabanan, 2023)
This study aims to determine how marketing strategies by optimizing the use of social commerce in the form of Tiktok for MSMEs in the Marketing 4.0 era. This research was conducted on consumers of Toko Enam in Tabanan Regency with a sample of informants obtained were consumers who shopped directly to the place as many as 10 people and filled out a questionnaire as many as 50 people so the total was 60 people. The results of this study found 3 new findings related to optimizing the use of social commerce as a marketing strategy, namely first, there is word of mouth marketing (WOMM) carried out by Toko Enam, second, there is a new customer path or New Customer Path 5A of Toko Enam consumers, namely Toko Enam consumers before buying products, they tend not to be sure first but ask their friends first, or read testimonials on social media related to the products they will buy. Third, Brand Value, namely, Toko Enam has more value for the goods sold or can be referred to as brand value where consumers not only choose the products sold, but reflect the quality, appropriate price, satisfaction in using the product, following current trends, and increasing social status and reputation.